2011
DOI: 10.2308/bria-50022
|View full text |Cite
|
Sign up to set email alerts
|

Does Wrongdoer Reputation Matter? Impact of Auditor-Wrongdoer Performance and Likeability Reputations on Fellow Auditors' Intention to Take Action and Choice of Reporting Outlet

Abstract: We investigate the effects of auditor-wrongdoer reputations for performance and likeability on fellow auditors' intentions to take action in response to a questionable audit act. We also use this context to explore auditor selection of reporting outlets, when they do choose to take action. In an experiment with 181 auditors, main effects suggest that likeability reputation is a significant determinant of intention to take action, while performance reputation is marginally significant. As expected, interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 39 publications
2
36
0
2
Order By: Relevance
“…In neither case is the reporter's identity disclosed to the perpetrator. Prior research (Robertson et al 2011;Curtis and Taylor 2009) has found no significant difference between whistleblowing likelihood under protection versus anonymity. To further this line of research, we present results analyzing likelihood under identity protection, where identity is protected from disclosure beyond the hotline, and under anonymity, where identity is not available to responders to hotline reports.…”
Section: Dependent Variablementioning
confidence: 93%
See 1 more Smart Citation
“…In neither case is the reporter's identity disclosed to the perpetrator. Prior research (Robertson et al 2011;Curtis and Taylor 2009) has found no significant difference between whistleblowing likelihood under protection versus anonymity. To further this line of research, we present results analyzing likelihood under identity protection, where identity is protected from disclosure beyond the hotline, and under anonymity, where identity is not available to responders to hotline reports.…”
Section: Dependent Variablementioning
confidence: 93%
“…Consistent with the vast majority of prior ethics-related research, we employ a vignette followed by survey questions to elicit individual research participants' perceptions of a particular ethical dilemma and their anticipated reaction (Kaplan and Whitecotton 2001;Schultz et al 1993;Robertson et al 2011). The vignette used in this study involves the senior auditors observing either a manager or a peer throwing away review notes from the engagement partner, which should be answered and retained.…”
Section: Methods Instrumentmentioning
confidence: 99%
“…The interest of academics on this issue was indicated by the development and testing of several models of research associated with the intention to blow the whistle on audit firms Curtis and Taylor 2009;Robertson et al 2011;Seifert et al 2014;Curtis 2010, 2013;Wainberg and Perreault 2016). However, the existing models do not show how the role of the organizational support / team norms and moral intensity possessed the auditor to arrive at causal explanation and assessment of responsibility for the perceived mistakes that caused the auditor's decision to blow the whistle.…”
Section: Introductionmentioning
confidence: 99%
“…(Female audit senior)An audit partner in the panel session added:
It is preferable to report internally and give the firm a chance to correct the wrongdoing. (Male audit partner)
Many international audit organisations also have an anonymous ethics hotline for reporting wrongdoing by audit staff (KPMG, ; Robertson et al ., ). Once the audit member has reported internally (step 4), (s)he expects corrective action to be taken within a reasonable period of time.…”
Section: Whistle‐blowing Framework On Misdeeds Committed By Audit Peersmentioning
confidence: 97%
“…() further find auditors in a principle‐based climate to be more likely to report wrongdoing compared to their colleagues in a rule‐based climate. Robertson, Stefaniak and Curtis () look at the relationship between reputation of wrongdoer and the preferred channel of reporting, and they find the former to be a significant predictor of auditors' intentions to take action, and this will more likely be through internal channels.…”
Section: Whistle‐blowing In An Auditing Contextmentioning
confidence: 99%